2018
DOI: 10.1111/1556-4029.13949
|View full text |Cite
|
Sign up to set email alerts
|

Trace Evidence Potential in Postmortem Skin Microbiomes: From Death Scene to Morgue

Abstract: Microbes can be used effectively as trace evidence, at least in research settings. However, it is unknown whether skin microbiomes change prior to autopsy and, if so, whether these changes interfere with linking objects to decedents. The current study included microbiomes from 16 scenes of death in the City and County of Honolulu and tested whether objects at the scenes can be linked to individual decedents. Postmortem skin microbiomes were stable during repeated sampling up to 60 h postmortem and were similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 45 publications
1
42
0
4
Order By: Relevance
“…As body site drives the microbial community composition more than any other factor (Pechal et al, 2018), comparisons to other body sites may be limited. For example, body sites sampled for the internal organs and blood (Javan et al, 2016) or skin microbiome (Kodama et al, 2019) could harbor different microbial communities than the ones included in this study, and provide different predictive power using this modeling approach. Beta-dispersion among all body sites was significantly different, but mouth, nose, and ears from this data set showed the most potential for downstream forensic applications.…”
Section: Discussionmentioning
confidence: 99%
“…As body site drives the microbial community composition more than any other factor (Pechal et al, 2018), comparisons to other body sites may be limited. For example, body sites sampled for the internal organs and blood (Javan et al, 2016) or skin microbiome (Kodama et al, 2019) could harbor different microbial communities than the ones included in this study, and provide different predictive power using this modeling approach. Beta-dispersion among all body sites was significantly different, but mouth, nose, and ears from this data set showed the most potential for downstream forensic applications.…”
Section: Discussionmentioning
confidence: 99%
“…After death, these personalized skin microbial communities are overwritten by a succession of microbes that thrive on nutrient-rich cadaver resources. The timeframe in which the succession of decomposer microbes begins to erase the personalized signatures of the human skin microbiome is unknown, although mounting evidence suggests that it is after the first 48 h after death, at least in most indoor death scenarios [17,27]. However, most studies that investigate postmortem skin microbial succession for estimating PMI use donor bodies placed outdoors, which likely results in a different community of decomposer microbes Fig.…”
Section: Freshmentioning
confidence: 99%
“…do microbiome samples need to be collected at the scene or can they be collected at autopsy?" [27]. The identification of these practical needs is critical for new science to be incorporated into the forensic workflow.…”
Section: Needmentioning
confidence: 99%
See 1 more Smart Citation
“…Forensic microbiology represents a potential emerging discipline in which microorganisms serve as forensic tools or trace evidence. Advances in DNA sequencing technologies paired with increased understanding of the human microbiome have hinted at the possibility that the microbiome could be used as a biomarker of decay (3) and as trace evidence to link individual people to objects they have previously interacted with (59). Recent studies have also shown that the microbiome can be used to estimate the amount of time that has elapsed since death, referred to as the postmortem interval (PMI), allowing investigators to establish a potential timeline of death (3, 1016).…”
Section: Introductionmentioning
confidence: 99%